Pooling of urine specimens for PCR testing: a cost saving strategy for Chlamydia trachomatis control programmes - Peeling, R. W. (BMJ Group, 1998)
OBJECTIVES: To evaluate pooling of first catch urine (FCU) specimens as a cost effective strategy for chlamydia testing. METHODS: Mock specimens were pooled with and without dilution to determine optimal pool size and ease of work flow. The performance of the Amplicor Chlamydia trachomatis PCR assay on pooled specimens was compared with individual testing using 370 FCU specimens from asymptomatic men presenting to an STD clinic. Cost savings associated with pooling were estimated. RESULTS: Using mock specimens, the sensitivity and specificity of the Amplicor PCR assay were not affected by pool sizes of two and five, but at a pool size of 10 decreased sensitivity due to inhibition was observed in one of five mock pools when the pooling method which involved no dilution was used. Archived FCU specimens from a study of 370 asymptomatic men were combined consecutively into 74 pools of five and tested by PCR. Of the 18 pools that contained positive specimens, 17 were PCR positive. Compared with testing FCU specimens individually, pooling resulted in a sensitivity of 95%, specificity of 100%, and a cost savings of 57% based on reduced number of tests required. CONCLUSION: Depending on the prevalence of infection, pooling of FCU specimens for PCR testing may result in cost savings compared with testing specimens individually. Further evaluations to validate this strategy using fresh FCU specimens are needed.